2009
DOI: 10.1111/j.1365-2052.2008.01820.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for the introgression of Western NR6A1 haplotype into Chinese Licha breed associated with increased vertebral number

Abstract: There is evidence that NR6A1 is a strong candidate for being a causal gene underlying vertebral number in pigs. The Licha Black is one of the leanest Chinese indigenous pig breeds, having an average vertebral number of 21.5. The introgression of Western germplasm into Licha Black, resulting in increased vertebral number, has been assumed but is not confirmed. This study detected allele frequencies of the NR6A1 causative mutation (c.575T>C) in 519 pigs from three Western and seven Chinese breeds including Licha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 8 publications
2
47
0
Order By: Relevance
“…41 . Briefly, a 360 bp segment was amplified and cut into two pieces of 183 and 177 bp for allele C at the position of 299,084,752 bp on SSC1.…”
Section: Methodsmentioning
confidence: 99%
“…41 . Briefly, a 360 bp segment was amplified and cut into two pieces of 183 and 177 bp for allele C at the position of 299,084,752 bp on SSC1.…”
Section: Methodsmentioning
confidence: 99%
“…Mikawa et al (2007) showed that a missense mutation in the nuclear receptor subfamily 6, group A, member 1 (NR6A1) gene is the most probable causative mutation for the QTL on SSC1. This mutation is fixed for the allele associated with larger number of thoracic and lumbar vertebrae in most commercial pig breeds (Mikawa et al, 2007;Yang et al, 2009;Ruben et al, 2012), including Italian Large White (Fontanesi et al, manuscript in preparation). Therefore, this polymorphism is not suitable for association studies with production traits in these breeds.…”
Section: Introductionmentioning
confidence: 96%
“…However, genetic variation of NR6A1 / GCNF was not detected in today's commercial-breed pigs, and they have no fewer than 20 vertebrae. Interestingly, the number-increasing-type (Leu-type) alleles were also detected in some Chinese indigenous breeds, in which introgression of Western germplasm has occurred with aim of improving their productivity and the number of vertebrae has increased [8]. …”
Section: Introductionmentioning
confidence: 99%